PEMURIDAN DALAM PENDIDIKAN AGAMA KRISTEN BERDASARKAN MATIUS 28:19-20 SEBAGAI UPAYA MENINGKATKAN KEDEWASAAN IMAN PESERTA DIDIK - Lusiana; Delpa Sombo Madulu'; Jelsia Panggalo; Yuyun Paliran; Wanny Farma Kasi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study aims to examine the essence of discipleship based on Matthew 28:19–20 and its implications for Christian Religious Education as a means to enhance the faith maturity of learners. The study employs a qualitative approach using a library research method. Data were gathered through an examination of the Bible, theological texts, Christian Religious Education books, and scholarly articles relevant to the research theme. Content analysis was used to identify, interpret, and synthesize various concepts regarding discipleship from the perspective of Matthew 28:19–20. The findings indicate that discipleship serves as the theological foundation for Christian Religious Education, focusing on shaping disciples of Christ through teaching, modeling, mentoring, and character building. The implementation of discipleship plays a proven role in fostering learners' faith maturity through spiritual growth, character transformation, and the application of Christian values ​​in daily life. Furthermore, discipleship principles hold significant implications for the development of Christian Religious Education in the modern era, specifically through transformative learning, the strengthening of the teacher's role, curriculum development, the wise use of technology, and the cultivation of a school culture centered on the values ​​of Christ.